Trimetallic Au@Pd@Pt nanozyme-enhanced lateral flow immunoassay for the detection of SARS-CoV-2 nucleocapsid protein. Issue 48 (5th December 2022) - Sun, Yue; Xie, Zihao; Pei, Fubin; Hu, Wei; Feng, Shasha; Hao, Qingli; Liu, Bing; Mu, Xihui; Lei, Wu; Tong, Zhaoyang
Abstract : The rapid spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) seriously threatened global public health. Abstract : The rapid spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) seriously threatened global public health. Establishing a rapid and sensitive diagnostic test for early detection of the SARS-CoV-2 nucleocapsid protein is urgently required to defend against the pandemic. Herein, an enhanced lateral flow immunoassay (LFIA) was fabricated by trimetallic Au@Pd@Pt core–shell nanozymes for detection of the SARS-CoV-2 nucleocapsid protein. The Au@Pd@Pt nanozymes (Au@Pd@Pt NZs) synthesized via a one-pot method, with a dendrite morphology and uniform particle size, showed excellent peroxidase-like activity. Due to the perfect enzyme-like catalytic activity toward 3, 3′, 5, 5′-tetramethylbenzidine (TMB) in the presence of hydrogen peroxide (H2 O2 ), the catalytic signal could be generated even by a tiny amount of Au@Pd@Pt NZs accumulated on the test strip. Therefore, rapid detection with higher sensitivity was achieved. The Au@Pd@Pt NZs-based LFIA provided a quantitative range of 0.05–100 ng mL −1 with a limit of detection of 0.037 ng mL −1, which was 17-fold lower than the LFIA without enhancement. The average recoveries from spiked samples were in the range of 92.5–107.9% with relative standard deviations all less than 4%, indicating the reliability and repeatability of the proposed LFIA. Additionally, the proposed LFIA could report results within 30 min using a microplate reader. In conclusion, the Au@Pd@Pt NZs-LFIA is a rapid, simple, and sensitive method for detecting the SARS-CoV-2 nucleocapsid protein.